Generalized exfoliative skin rash as an early predictor of supratherapeutic voriconazole trough levels in a leukemic child: A case report - Ali Amanati; Parisa Badiee; Mehrzad Lotfi; Ahmad Monabati; Mohammad Ali Faghihi; Majid Yavarian; Nazafarin Hatami-Mazinani (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: Skin rashes, mostly seen in children and adolescents, are considered among the most common side effects of azole antifungals. Although therapeutic concentrations of voriconazole (VCZ) have been documented for infected skin, there is no evidence specifying whether specific dermatologic side effects could predict high VCZ serum concentration, especially in high-risk leukemic children. Case report: Herein, we report a unique skin side effect of VCZ in a 5-year-old boy with T-cell acute lymphoblastic leukemia (ALL) referred to Amir Medical Oncology Center in Shiraz, Iran. The patient experienced erythroderma and macular rashes shortly after VCZ consumption, leading to generalized exfoliative skin rashes. Concurrent to these skin manifestations, VCZ serum concentration reached the supratherapeutic levels despite the recommended VCZ doses. As a result, VCZ was withheld, and the patient was treated with caspofungin. The lesions were resolved gradually within 2 weeks, and the patient successfully completed his treatment course with caspofungin. Conclusion: The unique case presented in this study emphasizes the need for a high index of suspicion for VCZ toxicity in any patient with atypical dermatologic manifestations, especially generalized exfoliative skin rashes. Based on this report, VCZ supratherapeutic concentration could be predicted early in the course of treatment. Additional therapeutic dose monitoring should be considered to establish a confirmatory diagnosis. It is required to further investigate the toxic effect of high VCZ concentration on the skin epithelium.